Sustaining Tradition in Modern Times: The Educational System of Salafiyah Boarding School at Darul A’mal Metro City - Abdul Ghofururrohim; Amirudin; Jaenullah (CV. Creative Tugu Pena, 2025)
Salafiyah Islamic boarding schools (Pondok Pesantren Salafiyah) are traditional Islamic educational institutions that have long played a crucial role in preserving and developing Islamic teachings, particularly through the instruction of classical Islamic texts (kitab kuning) and other religious sciences. However, in the face of rapid technological advancement, evolving educational demands, and swift social change, these institutions encounter significant challenges. Despite this, Salafiyah pesantren continue to uphold deep-rooted Islamic values while preparing students (santri) to contribute meaningfully to both religious and societal spheres. Their sustained relevance in the modern era highlights their capacity to nurture not only religious scholarship but also practical skills and strong moral character. This study aims to analyze the existence and resilience of the Salafiyah pesantren education system amid the currents of modernization. Employing a qualitative research approach with a case study design, data were collected through observation, interviews, and documentation. Data validity was ensured through triangulation, and analysis was conducted using data reduction, data display, and conclusion drawing. The findings reveal that Pondok Pesantren Darul A’mal continues to implement traditional learning methods such as sorogan and bandongan, both of which remain effective for in-depth study of classical texts and religious sciences. Sorogan allows students to engage in individualized learning directly with a teacher, who provides immediate correction and guidance. In contrast, bandongan involves collective learning, where students listen to a teacher’s reading and explanation of texts, followed by group discussions. These complementary methods effectively enhance the students’ comprehension of Islamic knowledge, demonstrating the continued relevance of traditional pedagogical approaches in a modern educational context.